The formation of multiple pituitary pouches from the oral ectoderm causes ectopic lens development in hedgehog signaling‐defective avian embryos. Issue 12 (10th August 2020) - Taira, Yuki; Ikuta, Yuya; Inamori, Sachiko; Nunome, Mitsuo; Nakano, Mikiharu; Suzuki, Takayuki; Matsuda, Yoichi; Tsudzuki, Masaoki; Teramoto, Machiko; Iida, Hideaki; Kondoh, Hisato
Abstract: Background: Hedgehog signaling has various regulatory functions in tissue morphogenesis and differentiation. To investigate its involvement in anterior pituitary precursor development and the lens precursor potential for anterior pituitary precursors, we investigated Talpid mutant Japanese quail embryos, in which hedgehog signaling is defective. Results: Talpid mutants develop multiple pituitary precursor‐like pouches of variable sizes from the oral ectoderm (OE). The ectopic pituitary pouches initially express the pituitary‐associated transcription factor (TF) LHX3 similarly to Rathke's pouch, the genuine pituitary precursor. The pouches coexpress the TFs SOX2 and PAX6, a signature of lens developmental potential. Most Talpid mutant pituitary pouches downregulate LHX3 expression and activate the lens‐essential TF PROX1, leading to the development of small lens tissue expressing α‐, β‐, and δ‐crystallins. In contrast, mutant Rathke's pouches express a lower level of LHX3, which is primarily localized in the cytoplasm, and activate the lens developmental pathway. Conclusions: Hedgehog signaling in normal embryos regulates the development of Rathke's pouch in two steps. First, by confining Rathke's pouch development in a low hedgehog signaling region of the OE. Second, by sustaining LHX3 activity to promote anterior pituitary development, while inhibiting ectopic lens development. Key Findings: Talpid mutant Japanese quail embryos defective in hedgehog signaling develop multiple LHX3–expressing pituitary pouches, analogous to Rathke's pouch, at ectopic positions of the oral ectoderm. These pituitary pouches fail to maintain LHX3 and instead activate the transcription factors leading to lens development. Thus, hedgehog signaling regulates the pituitary development at least in two different steps, i.e., inhibition of ectopic pituitary pouch development, and maintenance of LHX3 expression.